Performance evaluation of the Turkish pension fund system - Tolga Umut Kuzubas; Burak Saltoğlu; Ayberk Sert; Ayhan Yüksel (Journal of Capital Markets Studies (JCMS), 2019)
Purpose - The purpose of this paper is to provide an in-depth performance evaluation of funds offered by the Turkish pension system. Design/methodology/approach - This paper compares aggregate fund index returns with the corresponding asset class returns, estimates a factor model to decompose excess returns to factor exposures, i.e., ß return and excess return originating from residual » and analyzes persistence of fund returns using migration tables and Fama-MacBeth regressions and tests for market timing ability. Findings - Majority of pension funds are unable to generate excess returns. Majority of funds are unable to generate a positive » and fund returns are predominantly driven factor exposures. There is evidence for slight persistence in returns, mainly due to factor exposures and funds do not exhibit market timing ability. Originality/value - In this paper, the authors perform an in-depth analysis of pension fund performance for the Turkish pension fund system. The authors identify weaknesses and strengths of the pension fund industry and provide policy recommendations for a better design of pension fund system.
Keywords: 330; Fund performance evaluation; Turkish pension system